Relative Contributions of Selected Teachers' Variables and Students' Attitudes toward Academic Achievement in Biology among Senior Secondary Schools Students in Ondo State, Nigeria - L. O. Gbore; C. A. Daramola (Arizona State University, 2013)
This study investigated the relative contributions of selected teachers variables and students attitude towards academic achievement in biology among senior secondary schools in Ondo State, Nigeria.  It involved descriptive survey research and ex-post facto research designs.  The sample, 360 respondents which consists of 180 biology teachers and 180 senior secondary school three students were randomly selected from 36 senior secondary schools from the three Senatorial Districts of Ondo State using stratified random sampling technique. Teachers teaching attitudinal scale, Science oriented attitudinal scale and an inventory which requested for data from records on students senior secondary school certificate examination grades in biology were used for data collection.  Data collected for the study were analyzed using correlation matrix and multiple regression analysis. The results showed that significant relationships existed among the independent variables and students academic achievement in biology.  Also 62.5% of the variance observed in students achievement in biology was explained by linear combination of the five predictor variables. Students attitude was the most potent contributor to the prediction. Teachers workload was the least contributor to the prediction.  It was recommended that constant workshops and seminars should be made available by government for teachers to attend for the improvement of their teaching skills.  Teachers and students were also charged to change their attitudes positively towards the teaching and learning of biology.